Caracterización fisicoquímica y cromatográfica de taspina de Croton cuneatus Klotzch (pumasacha) - Sánchez Guerra, Said Rafael (2022)
The Croton genus, belonging to the Euphorbiaceae family, has been the subject of physicochemical and biological studies, due to its ethnobotanical applications. The taspine alkaloid contained in this genus has a wide range of properties such as healing, antihemorrhagic, burns, antiangiogenic, antileukemic and antibacterial. The objective of the work was to characterize the taspine alkaloid isolate from the aqueous extract of the bark of Croton cuneatus collected in the community of Manacamiri, province of Maynas, Loreto, Peru. To extract the alkaloid, ethanol and chloroform and characterization by physicochemical and spectrophotometric methods were used. 2.432 g of tapin were extracted, whose yield was 0.23%; melting point was 252.88°C, optical rotation +7.6; the molecular weight was 369.71 g/mol. Rf values in dichloromethane-methanol (20:1) was 0.7; in chloroform-diethylamine (18:2) 0.5 and in chloroform-acetone (18:9) 0.15. The maximum wavelengths (?max) were the following: 246, 285, 297, 330, 346 respectively. The result obtained from the species under study fully coincides with the values of the standard Taspina isolated from Croton lechlerii (sangre de grado). In conclusion, the data obtained are promising and that the botanical species C. cuneatus would be an important source to isolate taspine for medicinal purposes.